The influence of implementing green accounting, material flow cost accounting and corporate social responsibility on financial performance - Permatasari, Agnes Mega; Pradnyani, Ni Luh Putu Sri Purnama; Cahyadi, Luh Diah Citraresmi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research aims to examine the effect of implementing green accounting, material flow cost accounting and corporate social responsibility on company financial performance. The population in this study are companies in various industrial sectors in the textile and garment sub-sector listed on the Indonesia Stock Exchange in 2018-2022. The sample was selected using a purposive sampling method with three criteria which resulted in 8 companies with 5 years of observation resulting in 40 samples that were worthy of observation. This research uses multiple regression analysis using the SPSS program. In this research, the green accounting variable is measured using the level of measurement method with a score of 0 if not disclosed, 1 if in narrative form, 2 if in image and narrative form, and 3 if in image, narrative and number form, material flow cost accounting variable using the MFCA cost flow matrix, the corporate social responsibility variable using the 2016 GRI Standard CSR disclosure and the financial performance variable using ROA. Based on the results of the analysis, it shows that the variables green accounting and material flow cost accounting have a positive effect on the company's financial performance, which means that when the company implements green accounting and material flow cost accounting well it will improve the company's financial performance. The corporate social responsibility variable has a negative effect on the financial performance of a company, which means that when a company implements corporate social responsibility it will reduce the company's financial performance because the resulting expense value will reduce the value of profits and reduce financial performance.